Amplicon-Based Analysis of the Fungal Diversity across Four Kenyan Soda Lakes. (5th May 2022) - Mwirichia, Romano
Abstract : Microorganisms have been able to colonize and thrive in extreme environments characterized by low/high pH, temperature, salt, or pressure. Examples of extreme environments are soda lakes and soda deserts. The objective of this study was to explore the fungal diversity across soda lakes Magadi, Elmenteita, Sonachi, and Bogoria in Kenya. A new set of PCR primers was designed to amplify a fragment long enough for the 454-pyrosequencing technology. Analysis of the amplicons generated showed that the new primers amplified for diverse fungal groups. A total of 153, 634 quality-filtered, nonchimeric sequences derived from the 18S region of the rRNA region were used for community diversity analysis. The sequence reads were clustered into 502 OTUs at 97% similarity cut-off using BLASTn analysis of which 432 were affiliated to known fungal phylotypes and the rest to other eukaryotes. Fungal OTUs were distributed across 107 genera affiliated to the phyla Ascomycota, Basidiomycota, Glomeromycota, and and other unclassified groups refred to as Incertae sedis. The phylum Ascomycota was the most abundant in terms of OTUs. Overall, fifteen genera ( Chaetomium, Monodictys, Arthrinium, Cladosporium, Fusarium, Myrothecium, Phyllosticta, Coniochaeta, Diatrype, Sarocladium, Sclerotinia, Aspergillus, Preussia, and Eutypa ) accounted for 65.3% of all the reads. The genus Cladosporium was detected across all the samples at varying percentages with the highest being water from Lake Bogoria (51.4%). Good's coverage estimator values ranged between 97 and 100%, an indication that the dominant phylotypes were represented in the data. These results provide useful insights that can guide cultivation-dependent studies to understand the physiology and biochemistry of the as-yet uncultured taxa.